The Development of South African Policy Planning : A Qualitative Text Analysis - Mikhaylov, Slava (World Bank, Washington, DC, 2018)
The evolution of South Africa’s strategic policy directions was analyzed through the application of natural language processing (NLP) techniques to the texts of the Reconstruction and Development Plan, Growth, Employment And Redistribution, the Accelerated and Shared Growth Initiative South Africa, the New Growth Path, and the National Development Plan. In statistical, probabilistic topic modeling analysis, nine topics are identified across all development plans. In the decreasing order of proportion of development plans’ documents, the topics relate to: climate change and resources; green economy; corruption and security; health; skills and training; economic growth; fiscal policy and macro-economy; reconstruction and democracy; and education. The study is a background note for the South Africa Systematic Country Diagnostic.